Robust Coordinated Designing of PSS and UPFC Damping Controller - Amin Safari (Institute of Advanced Engineering and Science, 2013)
This paper presents the simultaneous coordinated designing of the UPFC robust power oscillation damping controller and the conventional power system stabilizer. On the basis of the linearized Phillips-Herffron model, the coordinated design problem of PSS and UPFC damping controllers over a wide range of loading conditions and system configurations is formulated as an optimization problem with the eigenvalue-based multiobjective function which is solved by a particle swarm optimization algorithm (PSO) that has a strong ability to find the most optimistic results. The stabilizers are tuned to simultaneously shift the undamped electromechanical modes to a prescribed zone in the s-plane. To ensure the robustness of the proposed simultaneous coordinated controllers tuning, the design process takes into account a wide range of operating conditions and system configurations. The effectiveness of the proposed method is demonstrated through eigenvalue analysis, nonlinear time-domain simulation and some performance indices studies under various disturbance conditions of over a wide range of loading conditions. The results of these studies show that the PSO based simultaneous coordinated controller has an excellent capability in damping power system oscillations and enhance greatly the dynamic stability of the power system.